Correction: Authentication of Allium ulleungense, A. microdictyon and A. ochotense based on super-barcoding of plastid genome and 45S nrDNA. - Minyoung Lee; Hyo Young Lee; Jong-Soo Kang; Hyeji Lee; Ki-Jin Park; Jee Young Park; Tae-Jin Yang (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0294457.].